2018
DOI: 10.4103/ajns.ajns_376_16
|View full text |Cite
|
Sign up to set email alerts
|

Early surgical outcome of endoscopic third ventriculostomy in the management of obstructive hydrocephalus: A randomized control trial

Abstract: Background:Management of obstructive hydrocephalus is an important issue for the reduction of mortality and morbidity.Objectives:The aim of the present study was to assess the early surgical outcome of endoscopic third ventriculostomy (ETV) in the management of obstructive hydrocephalus.Methodology:This randomized controlled trial was conducted at the Department of Neurosurgery at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, from April 2009 to September 2010 for 1½ years. All patients presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…5 Rahman et al reported that the patients who underwent VPS had one epidural and one subdural bleeding (the latter resulted in death), while in the group that underwent ETV, only two unspecified intraoperative bleedings were observed. 14 Ul Haq et al reported the occurrence of one bleeding in each group of patients. 15 Even though we found no significant difference in intraoperative or postoperative bleeding events, patients who underwent VPS had clinically more severe bleedings, due to a higher occurrence of subdural and epidural hematomas, the need for new interventions, and even one death reported by Rahman et al 14 In the previous meta-analysis, there was a significant difference regarding postoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Rahman et al reported that the patients who underwent VPS had one epidural and one subdural bleeding (the latter resulted in death), while in the group that underwent ETV, only two unspecified intraoperative bleedings were observed. 14 Ul Haq et al reported the occurrence of one bleeding in each group of patients. 15 Even though we found no significant difference in intraoperative or postoperative bleeding events, patients who underwent VPS had clinically more severe bleedings, due to a higher occurrence of subdural and epidural hematomas, the need for new interventions, and even one death reported by Rahman et al 14 In the previous meta-analysis, there was a significant difference regarding postoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Considering 30 postoperative infections reported in all five RCTs, 93.3% occurred in patients with VPS. 4,5,[13][14][15] There was a significant reduction in the total number of postoperative infections favoring ETV (RR: 0.11; 95% CI: 0.04-0.33; p < 0.0001; I 2 ¼ 0%; ►Fig. 2B).…”
Section: Postoperative Infectionmentioning
confidence: 95%
“…1,31,32,38,39 Definitive measures refer to surgeries that seek to restore CSF circulation (endoscopic third ventriculocisternostomy -ETV-and ventriculoperitoneal/atrial shunt -VPS/VAS-) and tumor resection. 29,32,[40][41][42][43][44][45] There is still controversy regarding the opportune moment and the therapeutic measure of choice. Faced with this dilemma, several questions arise: 1.…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…As in pediatric patients, the trend of recent decades places ETV above VPS/VAS. [41][42][43][44] ETV is the procedure of choice for the treatment of symptomatic obstructive hydrocephalus due to primary and/or metastatic tumor lesions, presenting good efficacy and a low rate of complications. 32,[41][42][43][44] In cerebellar metastases, the performance of ETV is similar to VPS/VAS, but at a lower cost and with less morbidity.…”
Section: Adultsmentioning
confidence: 99%
See 1 more Smart Citation